Repercussões bioquímicas e reprodutivas de mães e descendentes após o consumo materno de dieta hiperlipídica em roedores: Revisão Sistemática - Souza, Rafaianne Queiroz de Moraes (2019)
Maternal exposure to the high-fat diet (HFD) during gestation or lactation can be harmful to both mother and offspring. The objective of this systematic review was to synthesize the available data on the effects of maternal HFD on the reproductive parameter and biochemical profile in rodents. The electronic search was performed in the PUBMED (Public/Publisher MEDLINE), EMBASE (Ovid) and Web of Science databases. Data from 76 studies showed that change in biochemical and reproductive parameters is dependent on the experimental design. Furthermore, the heterogeneity found in the studies makes it impossible to comparisons. In addition, studies often omit or neglect important information, such as a description of the diet or methodological details. These factors make it difficult to affirm the true effect of maternal HFD consumption for both mother and offspring.